Aggression among school children in Malaysia - Kong, Luo Lan; Abdullah, Maria Chong; Roslan, Samsilah (Universiti Putra Malaysia Press, 2012)
This study aimed to investigate the level of aggression among primary school children in Malaysia. A total of 450 students aged 11 were randomly selected from nine schools in the Selangor State to participate in this study. Children Aggression Inventory (CAI) was administered to collect data from the respondents. The reliability of the CAI in this study was found to be high (α = 0.90). The data obtained were analyzed using both descriptive and inferential statistics to address the research objectives. Findings from this study showed that the aggression level demonstrated by school children was moderate (M = 2.18, SD = 0.392). The highest mean score for aggressive behaviour exhibited by the children is hostility (M = 1.88, SD= 0.37), followed by anger (M = 1.86, SD = 0.36), verbal aggression (M = 1.71, SD = 0.37), indirect aggression (M = 1.66, SD = 0.38), and physical aggression (M = 1.66, SD = 0.45). Results also indicated a significant difference between the boys and girls in the mean scores of physical aggression [t (443) = 6.034, p < 0.01] and anger [t (445.78) = -3.034, p < 0.01]. Boys were found to be more aggressive than girls in terms of physical aggression while girls were found to be more aggressive than boys in terms of anger.